Exploring the relationship between first‐year nursing student self‐esteem and dropout: A cohort study. (3rd March 2021) - Dancot, Jacinthe; Pétré, Benoît; Dardenne, Nadia; Donneau, Anne‐Françoise; Detroz, Pascal; Guillaume, Michèle
Abstract: Aim: To describe nursing student self‐esteem prior to the influence of nursing education and to explore the relationship between self‐esteem and dropout. Design: Cohort study. Methods: At the beginning of their first year of study, in October 2017, 464 nursing students completed a questionnaire that assessed their self‐esteem level via Tafarodi & Swann Scale and self‐esteem profile following Mruk's model, along with sociodemographic information, state anxiety, self‐efficacy, intention to continue and social support. One year later, data on grades and re‐enrolment were collected. Multivariate analyses explored the factors influencing self‐esteem level (multiple regression), self‐esteem profile (multinomial logistic regression) and dropout (binary logistic regression). Results/Findings: The mean level of self‐esteem was 50.8 (9.0), scale of 16 to 80. Forty‐nine per cent of self‐esteem profiles were classified as 'high', 20.1% as 'defensive acceptance based', 11.2% as 'defensive achievement based' and 19.6% as 'low'. State anxiety ( p < 0.0001), self‐efficacy about completion of the nursing programme ( p < 0.0001) and self‐efficacy about internship ( p < 0.0001) were associated with self‐esteem. The dropout rate was 21.5%. Self‐esteem level ( p = 0.039) and academic performance ( p < 0.0001) were associated with dropout. Conclusion: While nursing student self‐esteem is often described as low, we know little about its baseline before entering the nursing programme and the factors that influence it. The dropout rate among first‐year nursing students is high, but self‐esteem is rarely explored as a possible explanation. We found that students had medium, and potentially fragile, self‐esteem when starting their nursing education, and that self‐esteem was associated with dropout. Impact: Given that association and the impact of self‐esteem on well‐being and professional behaviour, educational institutions should foster self‐esteem both generally and in students with anxiety or low self‐efficacy. Future research should explore nursing student self‐esteem using a longitudinal mixed methods approach. Society should value nurses and nursing students.